A serpiginous lesion of scrotum - Sara Romano; Roberto Dall'Amico; Valentina Declich; Egidio Barbi (BMC, 2022)
Abstract Background Median raphe cyst is usually benign and asymptomatic male genitalia lesions. Although uncommon, infection may be a complication. Case presentation We report the case of a 4-year-old child presented to the emergency department for a serpiginous and redness lesion extended from the basis of the penis until the perineum. An infected median raphe cyst was suspected, and the patient underwent surgical treatment and antibiotic therapy with complete resolution of symptoms. Liquid culture resulted positive for Serratia Marcescens. Conclusion Infection is a rare complication, especially in childhood. To prevent relapses and clinical symptoms, the majority of authors recommend surgical excision followed by primary closure. In case of infections caused by Serratia Marcescens, chronic granulomatous disease should always be rule out.